2017
DOI: 10.1108/vjikms-09-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Ability-based emotional intelligence and knowledge sharing

Abstract: Purpose The purpose of this paper is to test the direct effects of emotional intelligence and trust in co-workers on knowledge sharing. Further, it aims to examine the moderating effect of trust in co-workers on the emotional intelligence-knowledge sharing relationship. Design/methodology/approach Data were collected from 121 employees working with 13 different service sector organizations in the northern region of India. The data were tested for validity and reliability. Hierarchical regression analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…The results obtained give credence to the fact that benevolence-based trust and competence-based trust in peers have a significant positive relationship with knowledge contribution and knowledge-seeking behavior of employees. These results are also in line with findings of earlier studies (Ansari and Malik, 2017;Chowdhury, 2005;Gillani et al, 2018;Swift and Hwang, 2013;Usoro et al, 2007;Wang et al, 2012;Zhang and Chen, 2018). It is interesting to find that the effects of different types of trust vary depending on what behavioral aspect of knowledge sharing the employee is engaged in.…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained give credence to the fact that benevolence-based trust and competence-based trust in peers have a significant positive relationship with knowledge contribution and knowledge-seeking behavior of employees. These results are also in line with findings of earlier studies (Ansari and Malik, 2017;Chowdhury, 2005;Gillani et al, 2018;Swift and Hwang, 2013;Usoro et al, 2007;Wang et al, 2012;Zhang and Chen, 2018). It is interesting to find that the effects of different types of trust vary depending on what behavioral aspect of knowledge sharing the employee is engaged in.…”
Section: Discussionsupporting
confidence: 93%
“…During the past 20 years, knowledge management and its role in success of the organizations and how those can gain sustainable competitive advantage have been studied widely (Drucker, 2001; Holsapple and Joshi, 2000). Especially the role of knowledge sharing among members of organizations has gained wide attention within academia (Ansari and Malik, 2017). It has been found that knowledge sharing contributes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…to the formation of novel ideas as well as to how new opportunities are developed (Lin, 2007), and different kind of organizations are constantly trying to provide completely novel or improved goods and services. To be successful in this, they need to create a knowledge sharing culture (Ansari and Malik, 2017). In that, the trust within an organization plays a major role (Lin, 2007; Vanhala and Ritala, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Edward and Natalija [11] investigated the importance of the role of emotional intelligence in negotiation and mediation considering the ability of intelligence to optimize the emotional climate in negotiation and mediation. Ansari and Malik [12] analyzed the relationship between emotional intelligence and knowledge sharing and tested the direct effects of emotional intelligence on knowledge sharing among co-workers.…”
Section: Literature Reviewmentioning
confidence: 99%